C-->U editing of apolipoprotein B mRNA in marsupials: identification and characterisation of APOBEC-1 from the American opossum Monodelphus domestica. - Fujino, T (1999)
The C->U editing of RNA is widely found in plant and animal species. In mammals it is a discrete process confined to the editing of apolipoprotein B (apoB) mRNA in eutherians and the editing of the mitochondrial tRNA for glycine in marsupials. Here we have identified and characterised apoB mRNA editing in the American opossum Monodelphus domestica. The apoB mRNA editing site is highly conserved in the opossum and undergoes complete editing in the small intestine, but not in the liver or other tissues. Opossum APOBEC-1 cDNA was cloned, sequenced and expressed. The encoded protein is similar to APOBEC-1 of eutherians. Motifs previously identified as involved in zinc binding, RNA binding and catalysis, nuclear localisation and a C-terminal leucine-rich domain are all conserved. Opossum APOBEC-1 contains a seven amino acid C-terminal extension also found in humans and rabbits, but not present in rodents. The opossum APOBEC-1 gene has the same intron/exon organisation in the coding sequence as the eutherian gene. Northern blot and RT-PCR analyses and an editing assay indicate that no APOBEC-1 was expressed in the liver. Thus the far upstream promoter responsible for hepatic expression in rodents does not operate in the opossum. An APOBEC-1-like enzyme such as might be involved in C->U RNA editing of tRNA in marsupial mitochondria was not demonstrated. The activity of opossum APOBEC-1 in the presence of both chicken and rodent auxiliary editing proteins was comparable to that of other mammals. These studies extend the origins of APOBEC-1 back 170 000 000 years to marsupials and help bridge the gap in the origins of this RNA editing process between birds and eutherian mammals.